2014
DOI: 10.1007/s00404-014-3379-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the pan neuronal marker PGP9.5 by immuno-histochemistry and quantitative PCR in eutopic endometrium from women with and without endometriosis

Abstract: PGP9.5 mRNA expression is increased in the proliferative phase of endometriotic women with pain. The presence of nerve fibres was demonstrated by a PGP9.5 protein signal in immuno-histochemistry and restricted to patients with endometriosis. Based on these results, however, there did not appear to be a direct association between the gene expression and protein abundance in women with and without endometriosis or those that experienced pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Other studies confirmed that the presence of nerve fibers demonstrated by immunohistochemistry was restricted to patients with endometriosis [7,15]. Additionaly, determining the density of nerve fibers can be a reliable marker for diagnosis of endometriosis [13].…”
Section: Resultsmentioning
confidence: 71%
“…Other studies confirmed that the presence of nerve fibers demonstrated by immunohistochemistry was restricted to patients with endometriosis [7,15]. Additionaly, determining the density of nerve fibers can be a reliable marker for diagnosis of endometriosis [13].…”
Section: Resultsmentioning
confidence: 71%
“…They found that the detection of nerve fibers in the eutopic endometrium with PGP 9.5 and neurofilament was not helpful in the diagnosis of endometriosis. Zevallos et al [12] studied the eutopic endometrial curettage of 29 patients: 16 women with endometriosis and 13 women without endometriosis. They did not find a significant difference in PGP 9.5 demonstrated fibers.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Progesterone treatment revealed a decrease in endometrial nerve fibers, but no clinical significance was identified. [17] As a result, further studies were recommended in recent publications for these patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, in women with peritoneal endometriosis no correlation was found between the presence of nerve fibers within the eutopic uterus and symptoms (Leslie et al, 2013; Zevallos et al, 2015). In another study, no statistical differences were found between eutopic uterus innervation density in women with endometriosis and pain verses other conditions, such as adenomyosis or uterine fibroids and pain (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%